2018
DOI: 10.1242/jeb.171488
|View full text |Cite
|
Sign up to set email alerts
|

Coping with the climate: Cuticular hydrocarbon acclimation of ants under constant and fluctuating conditions

Abstract: Terrestrial arthropods achieve waterproofing by a layer of cuticular hydrocarbons (CHCs). At the same time, CHCs also serve as communication signals. To maintain waterproofing under different climate conditions, insects adjust the chemical composition of their CHC layer, but this may affect the communication via CHCs. The detailed acclimatory changes of CHCs and how these influence their physical properties are still unknown. Here, we studied acclimation in two closely related ant species with distinct CHC pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 51 publications
(74 reference statements)
4
62
0
Order By: Relevance
“…Our study is the first social insect study to link variation in cuticular hydrocarbons with variation in colony productivity, although previous social insect studies have linked variation in cuticular hydrocarbons to worker survival (Sprenger et al 2018) or to climatic or biotic variation (Menzel et al 2017;Buellesbach et al 2018;Sprenger et al 2018 Interestingly, we found similar linear selection patterns using both definitions, as all significant linear estimates were in the same direction between the two definitions (Figure 3, Supplement table 2). This suggests that the hydrocarbon profile optima are largely aligned for the production of both reproductives and workers in our study population.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our study is the first social insect study to link variation in cuticular hydrocarbons with variation in colony productivity, although previous social insect studies have linked variation in cuticular hydrocarbons to worker survival (Sprenger et al 2018) or to climatic or biotic variation (Menzel et al 2017;Buellesbach et al 2018;Sprenger et al 2018 Interestingly, we found similar linear selection patterns using both definitions, as all significant linear estimates were in the same direction between the two definitions (Figure 3, Supplement table 2). This suggests that the hydrocarbon profile optima are largely aligned for the production of both reproductives and workers in our study population.…”
Section: Discussionsupporting
confidence: 59%
“…Knowledge of the fitness consequences of trait variation is necessary to characterize the type (e.g., directional, stabilizing, or disruptive) and strength of natural selection acting on a trait (Lande & Arnold 1983;Arnold & Wade 1984;Janzen & Stern 1998;Morrissey & Sakrejda 2013). Variation in the social insect hydrocarbon profile may affect individual survival and colony productivity by affecting desiccation resistance (Gordon 2013;Buellesbach et al 2018;Sprenger et al 2018;Friedman et al 2019) or by influencing chemical communication among nestmates and the collective behavior of the colony (Lahav et al 2001;Green & Gordon 2003;Martin & Drijfhout 2009a;Liebig 2010;Buellesbach et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This higher level of methyl‐branched CHCs underlies the significant higher desiccation resistance in D. serrata as compared to D. birchii . Similarly, CHC differences in two widely distributed ant species, Myrmica rubra and Myrmica ruginodis , are correlated with desiccation resistance …”
Section: Mechanisms Underlying How Climate Change Can Affect Insecticmentioning
confidence: 95%
“…36 Similarly, CHC differences in two widely distributed ant species, Myrmica rubra and Myrmica ruginodis, are correlated with desiccation resistance. 37 What do CHCs and desiccation resistance have to do with insecticide resistance? As mentioned earlier, in addition to target-site and metabolic resistance, reduced insecticide penetration has also been suggested to be a mode of insecticide resistance.…”
Section: Humidity Desiccation Resistance and Insecticide Pentrationmentioning
confidence: 99%
“…Queens forage for just a few weeks in early spring and cease to leave their nests after provisioning the first brood of the year, indicating a lower demand for desiccation resistance and, consequently, a smaller amount of CHCs. Indeed, the CHC profiles of insects have previously been shown to depend on climatic conditions, whereas a higher temperature leads to higher amounts of CHCs [49]. This might also be the reason for the higher amount of especially long-chain CHCs in workers compared with queens, because CHCs with a higher chain length are known to provide better waterproofing for the insect and therefore better drought resistance [49,50].…”
Section: Discussionmentioning
confidence: 99%